Rooted in Nanyang: Localization in Yuan Shang Cao's short stories - Zhu, W.; Fan, P.S. (Central China Normal University, 2016)
Yuan Shang Cao is an outstanding Malaysian Chinese writer in the early stages of the Malaysian Chinese literary movement. He plays an important role in directing the Malaysian Chinese literature towards a more Malaysian orientation. His short stories demonstrate a tendency of localization mainly in three distinct ways: a sharp focus on and strong emotional engagement with the local milieu; an indigenous perspective in the description of the Malaysian Chinese community; and the liberal use of the Hakka dialect in description of the Malaysian Chinese life experience.